2020
DOI: 10.7759/cureus.9716
|View full text |Cite
|
Sign up to set email alerts
|

Incidental PET/CT Findings of Suspected COVID-19 in a Region of High Prevalence

Abstract: We describe a case of suspected COVID-19 pneumonia in a 61-year-old male with known primary central nervous system diffuse large B-cell lymphoma (DLBCL) who underwent restaging PET/CT during the initial peak of infection of COVID-19 pneumonia within the New York region. At the time of his routine PET-CT to assess for disease progression, typical CT imaging features of COVID-19 pneumonia were identified. Upon further investigation, the patient was asymptomatic, and his infection status remained unknown. He was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…All of the patients with findings suggestive of COVID-19 infection were confirmed positive upon further workup. Mo et al [ 66 ] reported similar findings in another asymptomatic 60-year oncology patient in the United States with human papillomavirus, and Franceschi et al [ 67 ] reported a similar scenario in an asymptomatic 61-year-old patient with treated primary diffuse large B-cell lymphoma. Wakfie-Corieh et al [ 68 ] retrospectively reviewed 1079 oncologic 18 F-FDG PET-CT scans performed between February 2 and May 18, 2020 to identify lung and extraparenchymal lung involvement in asymptomatic cancer patients with COVID-19.…”
Section: Asymptomatic Covid-19 Oncology Patientsmentioning
confidence: 75%
See 2 more Smart Citations
“…All of the patients with findings suggestive of COVID-19 infection were confirmed positive upon further workup. Mo et al [ 66 ] reported similar findings in another asymptomatic 60-year oncology patient in the United States with human papillomavirus, and Franceschi et al [ 67 ] reported a similar scenario in an asymptomatic 61-year-old patient with treated primary diffuse large B-cell lymphoma. Wakfie-Corieh et al [ 68 ] retrospectively reviewed 1079 oncologic 18 F-FDG PET-CT scans performed between February 2 and May 18, 2020 to identify lung and extraparenchymal lung involvement in asymptomatic cancer patients with COVID-19.…”
Section: Asymptomatic Covid-19 Oncology Patientsmentioning
confidence: 75%
“…Infection with COVID-19 may remain asymptomatic and appears as incidental findings in nuclear imaging procedures performed for standard oncologic indications[ 63 - 67 ]. PET-CT findings are considered sensitive for the detection of early COVID-19 infection, even before its detection as nasal viral carriage[ 41 , 55 , 66 ].…”
Section: Asymptomatic Covid-19 Oncology Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently ongoing COVID-19 pandemic, has led to an increase in the number of CT scans performed due to a presumed diagnosis of pneumonia worldwide (8). This has caused various diseases and/or medical conditions to be noticed incidentally in CT examinations (15,16,17). On the other hand, this situation could be seen as an opportunity to retrospectively examine the relationships between various parameters through these CT scans with more objective measurements.…”
Section: Discussionmentioning
confidence: 99%